Tungsten dust in fusion tokamaks: relevant dust laser production, characterization and behaviour under tritium loading. (25th January 2016) - Bernard, E; Delaporte, P; Jambon, F; Rousseau, B; Grisolia, C; Chaudanson, D; Nitsche, S
Abstract: In this paper, production and study of tokamak relevant W particles is presented. Existing tokamak-produced dust being very scarce, extensive study of such nano-particles with high specific surface area (SSA) and sub micron size requires a specific and efficient alternative production technique, in order to obtain relevant particles to study. We present our production and collection setup based on pulsed laser ablation on bulk ITER-grade tungsten, and the various parameters impacting on the collected dust morphology and properties. We observed that optimum gas pressure is required to control the laser-induced plasma properties and favour the production of tungsten nano-particles with high SSA. The laser pulse duration is also a key parameter to limit the generation of tungsten liquid droplets during the ablation process. The nano-particules structure and general aspect are characterized via scanning electron microscopy and transmission electron microscopy. Lastly, this dust produced by laser ablation is loaded with tritium by gas exposure, and its retention capability and long-term evolution addressed and compared to metallurgically produced W powders with homogeneous size distribution.